Karakteristik Populasi dan Habitat Kelelawar Hipposideros cervinus (Sub ordo Microchiroptera) di Gua Bratus Kecamatan Air Besar Kabupaten Landak - Irwan Lovadi, Fetronius Piter, Tri Rima Setyawati (Universitas Tanjungpura, 2015)
Population characteristics is one of the efforts made to determine the presence of Hipposideros cervinus in a particularhabitat. This study aims to investigate the population characteristics of H. cervinus and physical characteristics ofBratus cave in Air Besar District, Landak Regency. The study was conducted by using Capture Mark Release Recapture method. Bats were caught in the web were marked with red oil paint on their digiti then released and recaptured again after 24 hours. The morphometrics of H. cervinus measured in this study are body length, wing span length, forearm length, fibula length, ears length, tail length, tarsometatarsus length, tarsometatarsus diameter, hind legs length without claws, hind legs length with the longest claws. The results show that the population of H. cervinus in the Cave of Bratus is 120 ind. Total number of H. cervinus found are 54 individuali consisted of 18 males and 36females with sex ratio of 1: 2. The temperature, humidity, light intensity, and wind speed at the Cave of Bratus ranging from 26o to 27oC, 87-94%, 8-12 lux, and 0 m/s respectively. Hence, environmental characteristics of the Cave of Bratus are suitable as habitat of H.cervinus.